2014
DOI: 10.1016/j.reprotox.2014.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Tetrabromobisphenol A activates inflammatory pathways in human first trimester extravillous trophoblasts in vitro

Abstract: Tetrabromobisphenol A (TBBPA) is a widely used flame retardant. Despite the presence of TBBPA in gestational tissues and the importance of proper regulation of inflammatory networks for successful pregnancy, there is no prior study on the effects of TBBPA on inflammatory responses in gestational tissues. The present study aimed to investigate TBBPA activation of inflammatory pathways, specifically cytokine and prostaglandin production, in the human first trimester placental cell line HTR-8/SVneo. TBBPA enhance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 88 publications
3
26
0
1
Order By: Relevance
“…This work was performed with the HTR-8/SVneo cell line (Graham et al, 1993). The HTR-8/SVneo cell line was derived from first trimester placentae and has provided a useful cell culture model for studies of EVT cellular responses (Liu et al , 2012; Wang et al , 2012; Weber et al , 2013) and initial investigations of toxicant actions on EVTs (Park et al , 2014a; Tetz et al , 2013a). …”
Section: Introductionmentioning
confidence: 99%
“…This work was performed with the HTR-8/SVneo cell line (Graham et al, 1993). The HTR-8/SVneo cell line was derived from first trimester placentae and has provided a useful cell culture model for studies of EVT cellular responses (Liu et al , 2012; Wang et al , 2012; Weber et al , 2013) and initial investigations of toxicant actions on EVTs (Park et al , 2014a; Tetz et al , 2013a). …”
Section: Introductionmentioning
confidence: 99%
“…Berveiller et al revealed the changes in some drug transporters during differentiation of cytotrophoblast to syncytiotrophoblast [27]. Park et al demonstrated that tetrabromobisphenol A increased some genes involved in inflammatory in first trimester extravillous trophoblast HTR-8/SVneo cells using a PCR array kit focused on an immune response pathway [28]. Using the drug transporter PCR array kit, we revealed that SLC7A11 was upregulated by treatment with AA and EPA.…”
Section: Discussionmentioning
confidence: 81%
“…In the present study, a PCR array kit was applied to thoroughly assess the profiles of transporter expression. There are many reports that investigate gene expression in a specific pathway by PCR array in various type of cells [25][26][27][28]. Berveiller et al revealed the changes in some drug transporters during differentiation of cytotrophoblast to syncytiotrophoblast [27].…”
Section: Discussionmentioning
confidence: 99%
“…Wykazano również zwiększoną ekspresję genów zaangażowanych w szlaki zapalne. Najniższe stęże-nie TBBPA, powodujące zmiany w aktywacji czynników prozapalnych, to 10 μM [55].…”
Section: Toksycznośćunclassified